Tenofovir and Emtricitabine: Impacts, demands and social challenges in antiretroviral treatment (Research, Society and Development, 2024)
The objective of this study was to evaluate the impact of the use of tenofovir and emtricitabine in the treatment of HIV patients on public health and on social and demographic implications. The study methodology is based on a literature review, with research carried out in the following databases: PUBMED, SCIELO (Scientific Electronic Library Online) and Google Scholar. Eighteen scientific articles were used. This study analyzed in detail the impact of the combination of tenofovir and emtricitabine in the treatment of HIV, highlighting its implications for public health and social and demographic dimensions. The research showed that, despite the proven efficacy of these drugs in viral suppression and increasing treatment adherence, there are challenges associated with their use. The combination of tenofovir and emtricitabine is widely used due to its efficacy and dosage convenience. However, treatment with these antiretrovirals faces challenges, such as potential renal and bone toxicity, drug interactions and the need for continuous monitoring. Treatment resistance, although less common, also represents an obstacle. The main need in HIV treatment is to achieve and maintain viral suppression. Tenofovir and emtricitabine offer a robust barrier to resistance, but challenges include potential toxicity and drug interactions. Substitution of tenofovir disoproxil fumarate (TDF) for tenofovir alafenamide (TAF) and implementation of educational programs are important strategies to improve adherence and minimize adverse effects.